KONFLIK PERIKANAN TANGKAP DI PERAIRAN KABUPATEN BENGKALIS PROVINSI RIAU - T. Ersti Yulika Sari; Sugeng Hari Wisudo; Daniel R. Monintja; Tommy Purwaka (Bogor Agricultural University, 2010)
The purpose of this study is to analyze the conflict in Bengkalis waters and contributing factors. Analysis of the conflict is descriptive and the factors that cause conflict with the approach of analyzed Fisher et al. (2000). The study was conducted in the waters Bengkalis Regency. The results showed that the conflict in Bengkalis waters began in 1983 to the present. This conflict started when hunting for kurau (Eleutheronema tetradactylum) in the waters of District Bantan began to rise. Primary factors driving the conflict has not received much attention and as basis for conflict resolution that remains in progress. These factors are identified into three parts: 1) cultural background, 2) social factors, and 3) juridical factor.